Development of the Clean and Healthy Living Behavior Improvement Model (PHBS) with a Teori Lawrence Green Approach to Santri in Islamic Boarding Schools - Khomsatun; Hamidi, A. Luthfi; Saryono; Siti Marpuah (Advances in Humanities and Contemporary Studies, 2024)
Santri is an adaptive learning person. In the concept of students or students, students have toughness when compared to ordinary students or non-students. This is what distinguishes the resilience of students with ordinary students, such as endurance, endurance of thinking, and resilience of creativity, because students are burdened with world knowledge (conventional sciences) and Islamic religious science. Therefore, in order to maintain this resilience, students must master a clean and healthy lifestyle that will affect body or physical resistance and mind resistance. This research uses qualitative research methods. The research technique or approach implemented in this research is by library research, which utilizes written objects in the form of books, journals that discuss the related topics studied. Data analysis in the deciphering of concepts in this study, also applied approaches or types of reflective conceptual research, or the application of ideas that had previously been explored by researchers by adjusting adjustments to conditions and situations related to the object of research. In relation to the object of research, researchers explore issues related to clean and healthy lifestyle models in Islamic boarding schools. From this problem, researchers will later describe it in the discussion section related to concepts that are parsed based on experience in the field. The results and discussions related to optimizing clean and healthy lifestyle models that can improve habits in clean and healthy living behavior, so as to avoid disease and be effective in learning.